Penerapan Problem-Based Learning dalam Studi Biofisika untuk Meningkatkan Kemampuan Berpikir Kritis Mahasiswa Pendidikan Sains - Muhammad Andika Putra; Madlazim Madlazim; Eko Hariyono; Mohammad Budiyanto (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates the effectiveness of Problem-Based Learning (PBL) in improving the critical thinking skills of science education students in a biophysics course. The research employed a pre-experimental design using the One Shot Case Study method with posttest-only data. The participants were fourth-semester undergraduate students from the Science Education Study Program at the State University of Surabaya, who took the Biophysics course in the 2023/2024 academic year. The study was conducted in June 2023. Data analysis using the Shapiro-Wilk test showed a significance value of 0.086, indicating that the data were normally distributed. A one-sample t-test yielded a significance value of 0.417, which supports the conclusion that PBL has a positive influence on students’ critical thinking skills. Overall, the implementation of PBL in biophysics lectures demonstrates its potential to enhance critical thinking among science education students.